Symmetry breaking and spin–orbit coupling for individual vacancy-induced in-gap states in MoS2 monolayers - Aliyar, Thasneem (2024)
Spins confined to point defects in atomically thin semiconductors constitute well-defined atomic-scale quantum systems that are being explored as single-photon emitters and spin qubits. Here, we investigate the in-gap electronic structure of individual sulfur vacancies in molybdenum disulfide (MoS2) monolayers using resonant tunneling scanning probe spectroscopy in the Coulomb blockade regime. Spectroscopic mapping of defect wave functions reveals an interplay of local symmetry breaking by a charge-state-dependent Jahn-Teller lattice distortion that, when combined with strong (≃100 meV) spin-orbit coupling, leads to a locking of an unpaired spin-1/2 magnetic moment to the lattice at low temperature, susceptible to lattice strain. Our results provide new insights into the spin and electronic structure of vacancy-induced in-gap states toward their application as electrically and optically addressable quantum systems.